IDENTIFIKASI POTENSI SUMBER ISOLAT PEMBENTUK GAHARU - Kusumaningsih, Karti Rahayu; Woesono, Hastanto Bowo; Hadi, Didik Surya (Jurnal Wana Tropika, 2019)
Right now, agarwood has very good prospect to be developed. To result agarwood resin, needs suitable inoculant that has high survival and can infect plant goodly. The purpose of this research is to identify of potency of several isolates source as agarwood inducer. This study used 3 isolates, namely Musa paradisiaca, Capsium frutescens and Pinus merkusii wood isolates which are made solid, mix and liquid inoculants. The observed parameters were identification of fungi, fungi growth, fungi spore density, and fungi attack infection length after 1 month inoculated. Results of the research showed that fungi at M. paradisiaca and C. frutescens isolates were Fusarium oxysporum, while at P. merkusii wood isolate was Ceratocystis sp. Musa paradisiaca and P. merkusii isolates had faster growth coloni than C. frutescens isolate. The highest fungi spore density resulted at M. paradisiaca isolate in mix inoculant. Three isolates had potency as agarwood inducer with 100% inoculation succcess percentage. Base on growth rapidly, spore density and easily reproduction, M. paradisiaca isolate was tend to chosen to be developed as inducer gaharu. Keywords : Identification, Isolates, Agarwood